2021
DOI: 10.1021/acsabm.0c01340
|View full text |Cite
|
Sign up to set email alerts
|

Scratching the Surface of Unventured Possibilities with In Situ Self-Assembly: Protease-Activated Developments for Imaging and Therapy

Abstract: In situ self-assembly has attracted increasing research interest for applications in imaging and therapy in recent years. Particularly for protease-activated developments, inspiration is drawn from the innate specificity of their catalytic activities, rapid discovery of the various roles they play in the proliferation of certain diseases, and inherent susceptibility of small molecule peptide conjugates to proteolytic digestion in vivo. The overexpression of a disease-related protease of interest can be exploit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 128 publications
0
7
0
Order By: Relevance
“…In the previous section, we discussed the assembled peptidenanomaterials that locate mitochondria. Recently, the in situ selfassembly attracts much attention due to its spatiotemporal precision and activable bioeffects, emerging as a frontier in the biomedical field (Deng et al, 2021;Kwek et al, 2021;Liu et al, 2021a;Wang et al, 2021b). The specific enzymes and overexpressed ROS can be used to trigger the self-assembly around or on the surface of mitochondria in situ.…”
Section: In Situ Self-assembly Of Peptide-nanomaterials In Mitochondriamentioning
confidence: 99%
“…In the previous section, we discussed the assembled peptidenanomaterials that locate mitochondria. Recently, the in situ selfassembly attracts much attention due to its spatiotemporal precision and activable bioeffects, emerging as a frontier in the biomedical field (Deng et al, 2021;Kwek et al, 2021;Liu et al, 2021a;Wang et al, 2021b). The specific enzymes and overexpressed ROS can be used to trigger the self-assembly around or on the surface of mitochondria in situ.…”
Section: In Situ Self-assembly Of Peptide-nanomaterials In Mitochondriamentioning
confidence: 99%
“…Peptide assemblies have emerged as a new class of biomaterials and have received increased research attention over the last two decades. 1−12 Since the seminal works demonstrated the applications of peptide assemblies in tissue engineering 13,14 and the report of exceptional self-assembling ability of short peptides, 15 peptide assemblies 16−23 have been explored for a wide range of applications, such as drug delivery, 24−26 cancer therapy, 27−32 optoelectronics, 33 cell cultures, 34,35 antibacterial, 36−38 immunomodulation, 39 molecular imaging, 40,41 and protein mimics. 8,42−44 Being encouraged by these rapid advances, we and Ulijn et al have shown the use of enzymatic reactions for generating peptide assemblies as a type enzymeresponsive biomaterials.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Although novel antibiotics and antimicrobial materials have made great strides in recent years, bacterial infection remains a clinical threat to human health. , It was reported that the number of deaths related to global antibiotic resistance will increase to 10 million per year by 2050 . Therefore, it is of great significance to develop safe, effective, less toxic, and nonantibiotic antibacterial strategies. , Traditional antibacterial polymer materials, including chlorhexidine, triclosan, polyethylenimide, etc., are mainly related to organelle modification and interference with bacterial intracellular biochemical pathways. They play an antibacterial role through the destruction of cell membrane, genes, protease, and other active substances . However, the development of polymer antibacterial materials is constrained by the difficulties, such as severe toxicity, poor heat resistance, quick breakdown, and the potential to induce microbial resistance. Alternatively, inorganic nanomaterials have been widely used in the field of tumor treatment and bacterial infection thanks to their low toxicity, good biocompatibility, easy modification, and large surface energy. Recently, various inorganic nanomaterials have been synthesized, including noble metal-based nanomaterials, , transition-metal-based nanomaterials, and other metallic nanomaterials .…”
Section: Introductionmentioning
confidence: 99%